Community strategies for intercultural participation - Casquilho-Martins, I.; Belchior-Rocha, H.; Ferreira, J. (Trabajo Social Global, 2020)
Faced with the demands of globalization Social Work has a key role in promoting community development. The relationship between Social Work and Human Rights focuses on values and principles essential to the integration of any person regardless of their social, economic, and cultural context. Through a study of social work praxis in an intercultural community context with immigrants, secondary statistical data were analysed, a semi-structured interview was applied to social workers and a categorical content analysis was chosen to treat the data. The results allowed us to realize that social workers appeal to an ethical and ontological matrix in relation to individuals, families, groups and communities and that community development intervention in the field of social policies implies participation strategies in favour of citizenship and Human Rights.